Increased expression of Forkhead box M1 transcription factor is associated with clinicopathological features and confers a poor prognosis in human hepatocellular carcinoma. Issue 11 (3rd February 2017) - Egawa, Mayumi; Yoshida, Yuichi; Ogura, Satoshi; Kurahashi, Tomohide; Kizu, Takashi; Furuta, Kunimaro; Kamada, Yoshihiro; Chatani, Norihiro; Hamano, Mina; Kiso, Shinichi; Hikita, Hayato; Tatsumi, Tomohide; et al.
Abstract : Aim: Forkhead Box M1 (FoxM1) is a proliferation‐specific transcription factor. In this study, we aimed to elucidate the clinicopathological and prognostic values of FoxM1 expression in human hepatocellular carcinoma (HCC) and correlate FoxM1 expression with various etiologies of liver diseases. We also investigated its therapeutic value in HCC. Methods: We investigated the expression of FoxM1 in tumor tissues and adjacent non‐tumor tissues of 79 Japanese HCC patients by quantitative real‐time reverse transcription–polymerase chain reaction analysis. Depletion by siRNA or specific inhibition by siomycin A were also used to investigate the effect of FoxM1 inhibition on stem‐like features of human HCC cells. Results: Quantitative real‐time reverse transcription–polymerase chain reaction analysis showed that tumor tissues displayed an approximately 14‐fold increase in FoxM1 expression compared with adjacent non‐tumor tissues. Interestingly, the expression levels of FoxM1in tumor tissues did not depend on the etiology of liver disease. The expression of FoxM1 in tumor tissues was associated with serum α‐fetoprotein level, maximum tumor size, histological grade, TNM staging, and portal involvement. Kaplan–Meier analysis indicated that the high FoxM1 expression (≥median) group had a poor prognosis compared with the low FoxM1 expression (<median) group. Using multivariate analysis, the expression of FoxM1 in tumor tissues was shown to be an independent prognostic factor that affected overall survival and disease‐free survival. Furthermore, FoxM1 inhibition by siRNA or siomycin A reduced spheroid colony formation of HCC cells in vitro . Conclusion: Our data suggest that FoxM1 might be a prognostic biomarker and a promising therapeutic target for HCC.